Synthesis of S-ligand tethered cellulose nanofibers for efficient removal of Pb(II) and Cd(II) ions from synthetic and industrial wastewater. (November 2018) - Abu-Danso, Emmanuel; Peräniemi, Sirpa; Leiviskä, Tiina; Bhatnagar, Amit
Abstract: Cellulose nanofibers (CNFs) tethered with sulphur as anionic ligand were synthesized from medical absorbent cotton by dissolution with NaOH, CO(NH2 )₂ followed by mechanical intrusion of sulphur from SC(NH₂)₂ at an elevated temperature. The solid-phase CNFs embedded with sulphur complexes possessed negative sites which were used to remove cationic metals viz., Pb(II) and Cd(II) from synthetic and industrial wastewater. The physicochemical properties of the CNFs were analyzed by Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), pH at point of zero charge (pHpzc ) and X-ray photoelectron spectroscopy (XPS). Batch adsorption studies were conducted with synthetic wastewater to optimize the conditions for Pb(II) and Cd(II) removal by CNFs. Different adsorption kinetic models were applied to assess and define the adsorption mechanism. The maximum Langmuir adsorption capacity was found to be 1.16 and 0.82 mmol g −1 for Pb(II) and Cd(II) ions, respectively. Regeneration studies showed that the CNFs can be reused using 0.1 M NaOH as eluent. The percentage removal efficiency of different cationic metals by CNFs from untreated industrial wastewater ranged from ca. 90–98%. Graphical abstract: Image Highlights: S-ligand tethered cellulose nanofibers were synthesized for metals adsorption. Adsorption capacity of S-CNFs was 1.16 mmol g −1 for Pb and 0.82 mmol g −1 for Cd. Ligand exchange is suggested as possible mechanism for both metal ions. Reusability studies revealed that synthesized adsorbent is resilient. Synthesized CNFs can be effectively used in industrial wastewater treatment. Abstract : In this work, anionic sulphur tethered cellulose nanofibers were synthesized from absorbent cotton and used in the removal of cationic metals from synthetic and industrial wastewater.